2000
DOI: 10.1021/jo000936q
|View full text |Cite
|
Sign up to set email alerts
|

New Crown Annelated Tetrathiafulvalenes:  Synthesis, Electrochemistry, Self-Assembly of Thiol Derivatives, and Metal Cation Recognition

Abstract: The synthesis of new S(2)O(4)-crown annelated tetrathiafulvalene (TTF) derivatives substituted with one terminal thiol group is described. Self-assembled monolayers (SAMs) of these compounds have been assembled on gold and platinum surfaces, the latter substrate giving improved quality films. SAMs of TTF derivative 16b are the most stable of those we have studied. Electrochemical data for SAMs of 5a, 5b, 8, 16a, and 16b in acetonitrile reveal two reversible one-electron waves, typical of the TTF system; the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 37 publications
2
35
0
Order By: Relevance
“…This limited stability has also been observed by Bryce and co-workers for similar compounds [14,16]. The importance of traces of moisture for the stability of the second redox process has been outlined by Khodorkovsky and co-workers [85].…”
Section: Oxidative Spectroelectrochemistrysupporting
confidence: 59%
See 1 more Smart Citation
“…This limited stability has also been observed by Bryce and co-workers for similar compounds [14,16]. The importance of traces of moisture for the stability of the second redox process has been outlined by Khodorkovsky and co-workers [85].…”
Section: Oxidative Spectroelectrochemistrysupporting
confidence: 59%
“…The non-aromatic 14 -electron system undergoes aromatisation when going from the neutral species to the dithiolium form in the singly and doubly oxidised states. TTF and its derivatives have featured in a wide variety of applications from crown-ether annelated electrochemical sensors [13][14][15][16], to molecular electronics [17][18][19][20][21] including organic field-effect transistors [22] and other advanced molecular assemblies [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Relatively recently, Reinhoudt et al (19)(20)(21)(22) and Bryce et al (23,24) reported, almost simultaneously, the incorporation of crownether groups into SAMs and their use as potential metal ion sensors. The Reinhoudt group used electrochemical impedance spectroscopy (EIS) for SAM characterization and to study the ion recognition processes (19)(20)(21)(22).…”
mentioning
confidence: 99%
“…25 and 26). The report by Bryce et al (23,24) described SAMs of crown-annelated tetrathiafulvalene (TTF) derivatives, which showed, by cyclic voltammetry (CV), a redox potential shift of the electroactive, surface-confined, crown-TTF group on ion complexation (23,24). The first TTF-crown SAMs reported by this group were apparently unstable after several electrochemical scans (23).…”
mentioning
confidence: 99%
See 1 more Smart Citation